(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The term ‘Hate Crime’ cannot be defined in limited words because the world resolves around only two words i.e. Love Hate. Love can create the things and hate always destroys the creativity. From decades the Love Peace both are vying hard will hate violence. The literal meaning of hate crime means a crime motivated by racial, sexual or other prejudice, typically one involving the violence. A hate crime is also known as a bias motivated crime or bias crime as it is a prejudice motivated crime usually violent, which occurs when a perpetrator targets a victim because of his as her membership (or perceived membership) in a certain social group or race. Generally these groups or violators target their victims which are almost exclusively limited to sex, ethnicity, disability, language, nationality, physical appearance, religion, gender identity or sexual orientation. Non- criminal actions that are motivated by these reasons are often called ‘bias incidents’.